2021
DOI: 10.4102/hts.v77i2.6619
|View full text |Cite
|
Sign up to set email alerts
|

Construction of rape culture amongst the Shona indigenous religion and culture: Perspectives from African feminist cultural hermeneutics

Abstract: Rape culture is reportedly prevalent in sub-Saharan Africa. Culture, patriarchy, poverty and religion continue to sustain rape culture. The notions of the objectification of women’s bodies amongst the Shona people are causatives for rape culture within diverse cultural institutions. Africans reasonably uphold marriage with high esteem; unfortunately, the marriage institution is also susceptible to becoming a source of abuse, coercion, and is often used as a tool for controlling women. Some of the entrenched ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Feminist interpretation therefore not only condemns the violence inflicted on the voiceless woman but also seeks to re-tell the story from her vantage point and portraying her as embodied cries of outrage (See also, Mwandayi & Chirongoma 2020;Sande & Chirongoma 2021). Assuming that the story is familiar to most people, we deliberately avoid re-telling it all over and move straight to look at how the Zimbabwean context of feminised violence is in dialogue with the Gibean incident of feminised violence.…”
Section: Feminist Hermeneutical Lenses On Judges 19-21mentioning
confidence: 99%
“…Feminist interpretation therefore not only condemns the violence inflicted on the voiceless woman but also seeks to re-tell the story from her vantage point and portraying her as embodied cries of outrage (See also, Mwandayi & Chirongoma 2020;Sande & Chirongoma 2021). Assuming that the story is familiar to most people, we deliberately avoid re-telling it all over and move straight to look at how the Zimbabwean context of feminised violence is in dialogue with the Gibean incident of feminised violence.…”
Section: Feminist Hermeneutical Lenses On Judges 19-21mentioning
confidence: 99%
“…Given that the underlying issue which comes out glaringly clear from Judges 19 is the lack of hospitality, the concubine's http://www.hts.org.za Open Access rape case beckons us to tap into a theology of hospitality and human dignity as springboards for addressing the rape culture in Zimbabwe. Writing specifically about the rape culture among the Shona people in Zimbabwe, Sande and Chirongoma (2021) put it across as follows:…”
Section: Towards a Theology Of Hospitality And Human Dignitymentioning
confidence: 99%
“…In the second part of the article, we then explore how these two women's experiences can be used as resources to seriously engage the problem of rape in contemporary Zimbabwe. The article draws to a close by countering the human rights violations, depravity and dehumanisations clouding the Judges 19-21 narrative and the case of Munengami, through proffering a theology of hospitality and human dignity as resources for reclaiming and restoring the humanity and dignity of women exposed to diverse forms of gender-based violence in our contemporary times (Mwandayi & Chirongoma 2020;Sande & Chirongoma 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This was exempli ed by Mutambare et al who found that, in Gweru, people living with HIV defaulted on medication use because they believed in faith healing, alternative medicines, and perceived spirituality as the main cause of HIV and AIDS (9). Other studies are limited to describing the role of religious stigma (10), religious norms associated with sexuality and gender (11,12,13,14,15), and the belief in witchcraft as the spiritual source of illness and health (16). Finally, Shoko points to the signi cance of traditional beliefs and practices by explaining that traditional medicine is important to Shona people because it addresses aspects which bio-medical practice fails to (17).…”
Section: Introductionmentioning
confidence: 99%